Evaluation of packing quality for types of pasta and noodles that available in the local markets (Journal of the College of Basic Education, 2024)
The quality of packaging of 21 types of pasta and noodles packed in flexible plastic bags and available in the local markets of Baghdad was evaluated. The results of the information label card scan showed that all samples contained the name of the material, the trade name, and the country of origin. However, the T5 sample was devoid of mentioning the producing company, also, T1, T5, T6, T7, T8 and T13 samples devoid of mentioned the batch number, while it was unclear in T17 and T18 samples. It was noted that there was a validity in the expired of samples, as it was 24 months in T1, T2, T3, T4, T5, T6, T7, T8, T9, T10, T11, T12 and T13, while it was 8 months in T14, T15 and T16 samples, it was 9 months in T17 and T18 samples, it was 8 months in T19, T20 and T21 samples, in while all forms contained a mention of storage conditions, warning signs, and weight, and the language of the label was Arabic and English, and the ingredients were mentioned in all forms except for form T5, which did not mention them. The laboratory tests showed that failed T1, T4, T5, T6, T7, T8, T9, T13, T14, T19 and T20 samples in passed the leakage test, while the samples T2, T3, T10, T11, T12, T15, T16, T17, T18 and T21 passed this test and whose welding test results were 5, 15, 143, 42, 89, 48, 95, 160, 67 and 58 mbar, respectively, while the thickness of the shell was 0.061, 0.060, 0.060, 0.054, 0.050, 0.071, 0.054, 0.062, 0.062, 0.230, 0.230, 0.231, 0.070, 0.041, 0.041, 0.042, 0.050, 0.050, 0.051, 0.050 and 0.050 µm for T1, T2, T3, T4, T5, T6, T7, T8, T9, T10, T11, T12, T13, T14, T15, T16, T17, T18, T19, T20 and T21 samples, respectively.